2012
DOI: 10.1039/c2sm25982f
|View full text |Cite
|
Sign up to set email alerts
|

Roles of gas in capillary filling of nanoslits

Abstract: International audienceControl and understanding of flows inside fabricated nanochannels is rich in potential applications, but nanoscale physics of fluids remains to be clarified even for the simple case of spontaneous capillary filling. This paper reports an experimental and modelling investigation of the role of gas on the capillary filling kinetics slowdown in nanoslits (depth going from 20 nm to 400 nm) compared to Washburn's prediction. First, the role of gas through the usually observed trapped bubbles d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 78 publications
0
52
0
Order By: Relevance
“…The front coefficient k in Eq. (1) varies depending on the geometry and the roughness of the channel walls [20], and was shown consistently less than what Lucas-Washburn equation (1) predicts [21]. In all these calculations, the effect of the finger part has been ignored.…”
Section: Introductionmentioning
confidence: 99%
“…The front coefficient k in Eq. (1) varies depending on the geometry and the roughness of the channel walls [20], and was shown consistently less than what Lucas-Washburn equation (1) predicts [21]. In all these calculations, the effect of the finger part has been ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, during the last decade different explanations have been proposed for the observed reduction in the capillary filling speed. Moreover, Chauvet et al 38 found that slower capillary filling rates cannot be explained by enhanced viscous resistance due to nanobubbles. Persson et al 30 extended the results reported by Tas et al 31 and concluded that other effects, different from the electroviscosity, also contribute to the observed deviations in the imbibition rates.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Tas et al 31 attributed the slower capillary rates to the electroviscous effect. Specifically, Chauvet et al 38 inferred that in sub 100 nm channels, the enhanced hydrodynamic resistance induced by the presence of nanobubbles is compensated for by the effect of the reduced volume to fill induced by the same gas nanobubbles. In the same context, Mortensen and Kristensen 37 found that the contribution of the electroviscous effect to the apparent viscosity is less than 1% and therefore concluded that the electroviscous effect is not sufficiently strong to account for the observed deviations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15.1a), which involve several technological steps: PM conception/realization and PR deposition, baking, insulating, and developing [8]. Typically, nanofluidic channels are made by using a conventional lithography step followed by dry or wet etching to define the depth of the channel [9]. Due to the limitations inherent to conventional lithographic processes, almost all nanofluidic devices have simple geometries with only one nanometric dimension, the channel depth.…”
Section: Tools For Nanosystems Prototypingmentioning
confidence: 99%